Progressive development and risk analysis of rock avalanches: a case study in Higher Himalayan Crystallines of the Langtang National Park, central Nepal - Weidinger, J. T. (Journal of Nepal Geological Society, 1998)
Basic research work on the rare phenomenon of the Tsergo Ri mass movement in the Upper Langtang valley (Nepal Himalaya) during 1990-1996 has helped to identify the most important causes of this extraordinary event (Weidinger et al., 1996). Further investigations all along the valley revealed the preexisting structures in the crystalline rocks of the Higher Himalayan sequence that are also responsible for smaller but frequent landslides and/or rock avalanches (Weidinger, 1997). Dynamic geomorphological changes are the result of weak rock behavior due to mechanical conditions of different lithology and seismotectonic structures. Rejuvenations of landslides and rockfalls are frequent as well. They often show a progressive development and/or continuous activity. Keeping in mind the preexisting structures of the Tsergo Ri landslide, which have been described as brittle reacting leucogranite dykes, metamorphites with deformational fabrics, sulphide ore and neotectonic structures, four recently occurred rockavalanches (typical for the Langtang Valley) were investigated: one in the right side of the recent Langtang valley glacier (Langtang Tsang), about 2 km north of the Alp Pangri Goldum, one in the area of the broken crest of the Tsergo Ri mass movement, west of the glacier named Kyimoshung Tsang (both in the Upper Langtang Valley) and two more in the Lower Langtang valley, south of the "Landslide Lodge" and north of the "Lama Lodge". Studying these phenomena from the geological and tectonical point of view, geomorphologic changes, morphodynamic development and triggering factors during a period of six years, made it possible to analyse future-risk for some parts of the area.